Glucocorticoids Regulate Circadian Rhythm of Innate and Adaptive Immunity - Shimba, Akihiro; Ikuta, Koichi (Frontiers in Immunology, 2020)
Animals have evolved circadian rhythms to adapt to the 24-h day-night cycle. Circadian rhythms are controlled by molecular clocks in the brain and periphery, which is driven by clock genes. The circadian rhythm is propagated from the brain to the periphery by nerves and hormones. Glucocorticoids (GCs) are a class of steroid hormones produced by the adrenal cortex under the control of the circadian rhythm and the stress. GCs have both positive and negative effects on the immune system. Indeed, they are well known for their strong anti-inflammatory and immunosuppressive effects. Endogenous GCs inhibit the expression of inflammatory cytokines and chemokines at the active phase of mice, regulating the circadian rhythm of tissue inflammation. In addition, GCs induce the rhythmic expression of IL-7R and CXCR4 on T cells, which supports T cell maintenance and homing to lymphoid tissues. Clock genes and adrenergic neural activity control the T cell migration and immune response. Taken together, circadian factors shape the diurnal oscillation of innate and adaptive immunity. Among them, GCs participate in the circadian rhythm of innate and adaptive immunity by positive and negative effects.